FORMULASI DAN EVALUASI SEDIAAN SABUN PADAT DENGAN VARIASI KONSENTRASI EKSTRAK DAUN SAGA (ABRUS PRECATORIUS L.): Formulation And Evaluation Of Solid Soap Preparations With Concentrations Of Saga Leaf Extract (Abrus Precatorius L.) - Natasya, Elvara; Putri P, Amanda Amelia; Afikasari, Dhian; Cahyaningsih, Seftiani; Fajar, Yusuf (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2025)
Saga leaves (Abrus Precatorius L.) are vines that originate from India. The leaves of the saga plant are known to be effective in treating diarrhea, tonsillitis, ulcers and hemorrhoids. The presence of secondary metabolite compounds which include saponins, flavanoids, alkaloids and steroids have antibacterial potential. The ain of this research is to find out how to make solid soap using saga leaf extract and evaluate the test results after making solid soap with saga leaf extract to determine the quality of the saga leaf extract solid soap preparation. The research method used was an experimental method with variations of saga leaf extract in three formulas, namely F1 1.5%, F2 2.5%, and F3 3.5%. the results showed that the solid soap was homogenous, in F1 it was yellow, F2 was mustard yellow, F3 was greenish yellow, had a typical vanilla odor, had a semi-solid texture, the average pH test results were respectively F1 11.59 ± 0.03, F2 11.81 ± 0.02, and F3 11.85 ± 0.01, average foam height test results F1 6.3 cm  ± 0.41 cm, F2 6.4 cm  ± 0.40 cm, F3 6.1 cm  ± 0.17 cm, average water content test results for F1 50.46%  ± 0.20%, F2 48.35%  ± 0.19%, and F3 45.55%  ± 0.24 %. Based on data analysis, if the test results show normal and homogeneous then the one-way the Kruskal-Wallis test can be continued. It is known that variations in the concentration of saga leaf extract have a significant effect on the organoleptic test, homogenity test, foam height test but not significantly on the pH test and water content test